2020
DOI: 10.1007/s42452-020-03447-x
|View full text |Cite
|
Sign up to set email alerts
|

Retreatability analysis of the Musina copper mine tailings in South Africa: an exploratory study

Abstract: In recent times, the potential beneficial uses of abandoned mine sites have been recognised and acted upon through the retreatment of tailings in order to win minerals of interest still available in economically viable concentrations. The most notable benefit (although not usually factored in financially) is that, once the tailings have been removed, the land has a greater potential to be developed further. The main aim of this study was to investigate the contents of copper and potentially harmful elements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The EIA and two invertebrate studies conducted for the MMSEZ failed to address the widespread use of natural resources by local communities for food, water, fuel, medicine, and cultural practices. During the Covid-19 pandemic, when sampling for the second invertebrate study by Singo (2021) was conducted, nature-based livelihoods from Pretoria northwards to the site of the MMSEZ and beyond to the Zimbabwean border were evident. Roadside hawkers were observed selling bundles of wildsourced Artemisia afra, a traditional remedy for flu (Ramalevha and Thompson 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The EIA and two invertebrate studies conducted for the MMSEZ failed to address the widespread use of natural resources by local communities for food, water, fuel, medicine, and cultural practices. During the Covid-19 pandemic, when sampling for the second invertebrate study by Singo (2021) was conducted, nature-based livelihoods from Pretoria northwards to the site of the MMSEZ and beyond to the Zimbabwean border were evident. Roadside hawkers were observed selling bundles of wildsourced Artemisia afra, a traditional remedy for flu (Ramalevha and Thompson 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Considering 127 women and three men were found camping and bulk collecting mopane worms on a single farm near Musina in the Limpopo province (Taljaard 2019), the public participation process of the EIA should have identified mopane worm users as I&APs. The substantial body of literature documenting the importance of mopane worms as a nutritional food and a source of income (Baiyegunhi and Oppong 2016;Egan et al 2014;Makhado et al 2009;Sekonya, McClure and Wynberg 2020;Taljaard 2019) was also excluded from the EIA and the invertebrate reports compiled by Greffrath (2019) and Singo (2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary resources have been overexploited, and for sustainable development of resources, the development and utilization of tailings have become urgent. A survey of the copper content in tailings of the Musina mine, an abandoned copper mine in the northern Limpopo Province, showed that the residual copper currently stands at 8,555 tons [52]. As ore grades continue to decline, the byproducts of foam flotation are expected to produce copper tailings that still contain large amounts of unrecovered copper [53].…”
Section: Research Hotspots Of Biological Leaching Technologiesmentioning
confidence: 99%